Der Briefwechsel zwischen Augustinus und Hieronymus und ihr Streit um den Kanon des Alten Testaments und die Auslegung von Gal. 2, 11-14 - Hennings, Ralph. (Vigiliae Christianae, Supplements, 1993)
This volume deals with the correspondence between Augustine and Jerome, discussing the way the letters were handed down to posterity, as well as their contents. In the first part it is shown that Jerome and Augustine both published a collection of the correspondence. In addition a list of manuscripts is given. The second part deals with the conflict between Augustine and Jerome. Not only their discussion whether the Hebrew Bible or the Septuagint should be considered canonically authoritative for the Church, but also their argument on the right exegesis of the quarrel between Peter and Paul in Antioch, whether Christians should observe the Jewish Ceremonial Laws (Gal. 2,11-14). The book is of particular interest for scholars in Patristic and Jewish Studies, giving a fresh approach to this important correspondence.